2015
DOI: 10.1586/14787210.2015.1068117
|View full text |Cite
|
Sign up to set email alerts
|

Tackling virological failure in HIV-infected children living in Africa

Abstract: Drug resistance in HIV-infected children is one of the main contributors to antiretroviral treatment (ART) failure, especially in developing countries. Sub-Saharan Africa has the largest burden of pediatric HIV infection in the world. Herein, we systematically review the current status of ART failure in HIV-infected African children. A literature search for publications within 10 years was performed through PubMed to identify relevant articles. Included studies examined the impact of timing of ART initiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 87 publications
(64 reference statements)
1
12
0
1
Order By: Relevance
“…The impact of DRMs acquired via prevention of mother-to-child transmission could not be evaluated in our study, but we previously reported a moderate (between 5% and 15%) prevalence of DRMs in the Central African HIV-infected pediatric population of Bangui. [96] These observations support the use of lopinavir-based 1st-line regimens in children in Africa as recommended by the WHO, [7,8,46,82,85,90,97] especially with the recent national recommendations to implement lifelong antiretroviral treatment for mothers. However, only 1 (12.5%) of the 8 children aged below 5 years was on a 1st-line PI-based antiretroviral treatment regimen in 2013 as recommended by the WHO, illustrating that these guidelines have not yet been implemented.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The impact of DRMs acquired via prevention of mother-to-child transmission could not be evaluated in our study, but we previously reported a moderate (between 5% and 15%) prevalence of DRMs in the Central African HIV-infected pediatric population of Bangui. [96] These observations support the use of lopinavir-based 1st-line regimens in children in Africa as recommended by the WHO, [7,8,46,82,85,90,97] especially with the recent national recommendations to implement lifelong antiretroviral treatment for mothers. However, only 1 (12.5%) of the 8 children aged below 5 years was on a 1st-line PI-based antiretroviral treatment regimen in 2013 as recommended by the WHO, illustrating that these guidelines have not yet been implemented.…”
Section: Discussionsupporting
confidence: 59%
“…During the last decade, the use of antiretroviral drugs was widespread in sub-Saharan Africa for preventing mother-to-child transmission, dramatically reversed the spread of HIV and significantly reduced the morbidity and mortality of this epidemic in the child population. [48] However, compared to adults, children living with HIV are less likely to receive antiretroviral treatment. [9] Furthermore, if the extension of access to antiretroviral drugs in African children has significantly reversed the infant mortality curve associated with AIDS, it has also facilitated emergence and spread of drug-resistant virus in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high VL among a patient with perfect adherence may indicate potential drug resistance. [11][12][13] Returning and discussing VL results with patients has been shown to be a tool to support viral resuppression since it provides an opportunity for providers to reinforce adherence. [14][15][16] Since adolescents will require treatment for years longer than adults, poor adherence, treatment failure and drug resistance can have more serious consequences making VL monitoring particularly important for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment efficacy is compromised by an inappropriate adherence to treatment and by the selection of resistant virus [5]. Since approximately one-third of HIV-infected children experience virological failure within two years of initiating cART [6], drug resistance mutation (DRM) monitoring should be performed at diagnosis and after therapy failure to optimize first and second or more-line regimens. However, resistance studies in paediatric infections worldwide are still scarce [7].…”
Section: Introductionmentioning
confidence: 99%